The Structure of Basic Level Categories in the Ukrainians’ Consciousness According to the Results of Psycholinguistic Experiments: PARKAN and MUR - Zhuykova , Marharyta; Lavrynovych , Liliia; Svidzynska , Olha (East European Journal of Psycholinguistics, 2020)
The aim of this research is to identify experimentally the structure (primarily the central zone) of two basic level categories in the Ukrainian speakers minds: PARKAN and MUR. To rich such an aim, two psycholinguistic experiments were developed and conducted. Within the first experiment the respondents were asked to determine whether the object on the picture belongs to the category PARKAN. Within the second one they were asked to determine whether the object on the picture belongs to the category MUR. For each experiment 75 images of the objects with similar functions and perceptual features were selected. The respondents had to choose integers 1-2-3 under the image, where 3 means that the object enters into the category, and 1 means that the object doesn't enter into the category. In the options of responses there was the possibility of partial and complete discrepancy between the word that names the category and the image. The total number of completed Google forms is 846, the total number of the received responses - 12690. The second experiment also took into account the estimates of the respondents from the control group which included 18 historians, architects and restorers. The scaling method was used to process the results: each object received an average score which determined its place in the structure of the category. The central zone of both categories includes objects with a score of 2.75 and higher. By analyzing the perceptual and functional features of the objects of the central zone we have formed a verbal description of the prototypes of the categories PARKAN and MUR. During the processing of experimental data there were found the differences in the principles of formation of the central zones of categories. This is related to the role of these objects in the modern anthropogenic landscape. The assignment of a certain artifact to the category PARKAN is influenced by two factors: perceptual features and function that a person derives from external features due to his/her background knowledge. When categorizing an object as a typical MUR not only perceptual features and function are important, but also information that goes beyond current knowledge about the world, namely knowledge about the status and functions of reality in the past. It is believed that information about the cultural and historical role of reality occupies an important place in the structure of the concept but our research has shown that such knowledge can affect the content and structure of not only concepts but also categories of consciousness.